Clinical utility of geriatric assessment tools in older patients with gastrointestinal cancer - Doi, Ayako; Mizukami, Takuro; Takeda, Hiroyuki; Umemoto, Kumiko; Arai, Hiroyuki; Horie, Yoshiki; Izawa, Naoki; Ogura, Takashi; Sunakawa, Yu (Frontiers in Oncology, 2023)
Background: Geriatric 8 (G8) and instrumental activities of daily living (IADL) are recommended to predict overall survival (OS) or risk of serious adverse events (SAEs) in older cancer patients. However, the clinical utility is relatively unknown in older patients suffering malnutrition with gastrointestinal (GI) cancer, including gastric cancer (GC) and pancreatic cancer (PC). Materials and Methods: We retrospectively included patients aged ≥65 years with GC, PC, and colorectal cancer (CRC) who received a G8 questionnaire at first visit from April 2018 to March 2020. The associations between G8/IADL and safety or OS were assessed in patients with advanced/unresectable tumors. Results: Of 207 patients (median age: 75 years), the median G8 score was 10.5 and normal G8 score rate was 6.8%. Both the median G8 score and normal G8 (>14) score rate numerically increased in the order of GC < PC < CRC. There was no clear association between the G8 standard cutoff value of 14 and SAEs or OS. However, OS was significantly longer in patients with G8 >11 than in those with G8 ≤11 (19.3 vs. 10.5 months, p = 0.0017). Furthermore, OS was significantly better in patients with normal IADL than in those with abnormal IADL (17.6 vs. 11.4 months, p = 0.049). Conclusion: The G8 cutoff value of 14 would not be clinically useful in patients with GI cancer for predicting OS or SAEs; however, the cutoff value of 11 and IADL may be useful to predict OS for older patients with GI cancers including GC and PC.